Biomechanical characterization of the backstroke start in immerged and emerged feet conditions - de Jesus, K.; de Jesus, K.; Figueiredo, P. A.; Gonçalves, P.; Pereira, S. M.; Vilas-Boas, J. P.; Fernandes, R. J. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The start is accepted as an important element for success in competitive swimming, especially in the short events. Concerning the backstroke start, the number of studies is scarce, none of which has yet dealt with the technical adjustments allowed by the new rules that authorize the swimmers to position their feet above water level. The aim of this study was to describe and compare two variants of the backstroke start technique, one with the feet parallel in complete immersion (BSFI) and the other with the feet parallel in complete emersion (BSFE) METHODS: Six male high-level swimmers performed two sets of 4 maximal intensity backstroke starts using the two variants: BSFI and BSFE (with intervals of 2 min between repetitions and 1 h between sets). Dual-media video images (Vilas-Boas et al., 1997) were recorded using two cameras (DCR-HC42E and SVHS-JVCGR-SX1) positioned in the sagittal plane of the movement and afterwards digitized (APAS). Kinetic data were obtained using an underwater extensometric platform. The handgrip system was adapted allowing keeping the same body elevation regarding water surface. The backstroke start was divided into three phases (adapted from Hohmann et al., 2006): hands-off, take-off and flight. Several temporal and kinematical parameters were assessed. RESULTS: Findings registered higher flight time and higher horizontal displacement of the centre of mass (Dx) at BSFI. BSFE seems to imply higher impulse, and higher time of hands-off, foot take-off and total start. DISCUSSION: As a performance parameter, the total time spent during the start was lower for BSFI than BSFE, allowing concluding that the first being faster than the second should be preferred for competitive use. This observed superiority of the BSFI may be at least partially justified by the higher flight time and Dx. These findings seem to confirm the hypothesis that lower feet position can determine the Dx by constraining the orientation of the resultant wall reaction vector. It is recommended that coaches begin monitoring the backstroke start variants strategies to improve tech nique, which can be determinant of the start success.